The Effect of Sustainable Finance and Green Innovation on ESG Performance With Foreign Experience CEO as a Moderator - Sofie Sofie; Yvonne Augustine (Cita Konsultindo Research Center, 2024)
The concept of sustainable ESG performance in companies can have the opportunity to provide various competitive benefits and influence the development of good values. ESG performance can mitigate financial risk during the financial crisis during the COVID-19 pandemic and reduce portfolio risk. In addition, companies that invest in ESG show that the company carries out ethical investment practices and can increase returns (Broadstock et al., 2021), thereby influencing the sustainability of the company and investors. This research aims to examine the influence of Sustainable Finance, Green Innovation, CEOs with foreign experience and the interaction of Sustainable finance and Green Innovation with CEOs on ESG performance using the control variables firm size and company age. The panel regression model is used because the data structure used is a combination of time series data and cross section data. The samples used in this research are companies listed on the Indonesia Stock Exchange in 2018 - 2021 for 2 types of industry, namely the banking sector and the development sector. The sampling technique used was purportive sampling. Based on the specified criteria, 22 mining companies and 34 banking companies were selected so that the total sample used in this research was 224 samples. The results of this research show that both the overall and partial tests of Sustainability Finance (SF) have proven to have a positive effect on ESG performance. Meanwhile, overall green finance has been proven to have no effect on ESG performance, but partially green innovation banking companies have proven to have a positive effect on ESG performance. CEOs with foreign experience have proven unable to moderate the influence of sustainable finance and green innovation on ESG performance. This research contributes to academic and practical literature related to efforts to achieve ESG performance.